1960
DOI: 10.1099/00221287-23-2-257
|View full text |Cite
|
Sign up to set email alerts
|

Replica Plating and Rapid Ascus Collection of Neurospora

Abstract: SUMMARYTwo colonial strains of Neurospora crmsa have been found suitable for testing nutritional requirements by replica plating. One strain (crisp) has been replicated with a set of needles and the other (crisp, ragged) with filter paper. When ripe perithecia from crisp x crisp crosses are submerged in water, complete asci can be collected rapidly with a capillary pipette.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1967
1967
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…A method using a board with closely arranged needles instead of velvet was invented by FORBES (as described by ROBERTS 1959) for replication of Aspergillus. It has also in some instances been of use for replication of Neurospora (MALING 1960).…”
Section: Replication By the Net Methodsmentioning
confidence: 99%
“…A method using a board with closely arranged needles instead of velvet was invented by FORBES (as described by ROBERTS 1959) for replication of Aspergillus. It has also in some instances been of use for replication of Neurospora (MALING 1960).…”
Section: Replication By the Net Methodsmentioning
confidence: 99%
“…Produces very short conidiophores, bearing conidia in tight clusters (610,611). Photographs (533,634). Recessive.…”
Section: Con-i: Recombination Control-1mentioning
confidence: 99%
“…Modifier mutations which alter morphology and the ability of cr-i to use glycerol occur frequently (383,905). Crosses homozygous for allele B123 exude intact linear asci (634). Double mutants sn cr and cr rg form small conidiating colonies suitable for replica plating with velvet (182,634,796,932,1020).…”
Section: Con-i: Recombination Control-1mentioning
confidence: 99%
“…Mackintosh & Pritchard (1963) found that with the induction of micro-colonies with sodium deoxycholate and the use of damp velveteen they were able to replica plate Aspergillus nidulans. Other methods have also proved effective -the use of a perspex block embedded with steel pins (Roberts, 1959) or filter paper (Maling, 1960), along with morphological mutants of Neurospora crassa, which produced restricted growth. Other methods have also proved effective -the use of a perspex block embedded with steel pins (Roberts, 1959) or filter paper (Maling, 1960), along with morphological mutants of Neurospora crassa, which produced restricted growth.…”
Section: Introductionmentioning
confidence: 99%